Spatiotemporal Expression of EAPP Modulates Neuronal Apoptosis and Reactive Astrogliosis After Spinal Cord Injury. Issue 7 (July 2015) - Chen, Minhao; Ni, Yingjie; Liu, Yonghua; Xia, Xiaopeng; Cao, Jianhua; Wang, Chengniu; Mao, Xingxing; Zhang, Weidong; Chen, Chen; Chen, Xinlei; Wang, Youhua
ABSTRACT E2F‐associated phosphoprotein (EAPP) is a novel E2F binding protein that interacts with the activating members of the E2F transcription factors family and involved in various biological processes. However, the expression and function of EAPP in central nervous system (CNS) are still unknown. In this study, we performed an acute spinal cord injury (SCI) model in adult rats, we found that EAPP protein levels were significantly increased and reached a peak at day 3, and then gradually returned to normal level at day 14 after spinal cord injury and we observed that the expression of EAPP is enhanced in the gray and white matter. Spatially, increased levels of EAPP were striking in neurons and astrocytes. Moreover, colocalization of EAPP/active caspase‐3 was detected in neurons, and colocalization of EAPP/proliferating cell nuclear antigen (PCNA) was detected in astrocytes after spinal cord injury. These results indicated that EAPP might play an important role in neuronal apoptosis and reactive astrogliosis. Furthermore in vitro, EAPP depletion by siRNA inhibited astrocyte proliferation, migration and CDK4/cyclinD1 expression. Meanwhile, EAPP knockdown also reduce neuronal apoptosis and cell cycle related proteins. Which indicated that EAPP might integrate cell cycle progression and play a crucial role in cell proliferation and apoptosis. Taken together, we speculated that EAPP was involved in biochemical and physiological responses after SCI. J. Cell. Biochem. 116: 1381–1390, 2015. © 2015 Wiley Periodicals, Inc.